Engineered gold nanoparticle-based miRNA precision regulation for tumor diagnosis and synergistic therapy - Li Chen; Haoyu Wang; Handan Zhang; Wenyun Mu; Xinran Shi; Xin Chen (Smart Materials in Medicine, 2025)
Cancer remains a major global health challenge, with traditional therapies such as chemotherapy, radiotherapy, and surgery often limited by side effects, drug resistance, and incomplete tumor eradication. Recent advances in molecular biology have highlighted the dual role of microRNAs (miRNAs) in cancer, acting both as oncogenes and tumor suppressors, thereby offering new avenues for targeted therapy. Due to their unique physicochemical properties, including excellent biocompatibility, surface functionalization capabilities, and photothermal effects, gold nanoparticles (Au NPs) have emerged as a promising platform for miRNA delivery. However, a systematic understanding of how to effectively design Au NPs-miRNA systems for integrated tumor diagnosis and therapy, and their synergistic effects with photothermal therapy, chemotherapy, and immunotherapy to enhance therapeutic efficacy, remains lacking. In this review, we comprehensively summarized the advantages and challenges of the current Au NPs-miRNA system and discussed its recent advances in tumor diagnosis and therapy.